Associations of different insulin resistance-related indices with the incidence and progression trajectory of cardiometabolic multimorbidity: a prospective cohort study from UK biobank - Zhenyu Tian; Lu Yang; Yifei Li; Yueqing Huang; Jianmin Yang; Fei Xue (Cardiovascular Diabetology)
Abstract Background Despite established associations between insulin resistance (IR)-related indices and cardiometabolic diseases (CMDs), most studies are limited to single CMD outcomes. The study aimed to examine the influence of IR-related indices on the incidence, predictive value, and progression trajectory of cardiometabolic multimorbidity (CMM), as well as potential biological mechanisms. Methods This prospective study included 374,274 individuals from the UK Biobank who were free of CMDs at baseline. CMM was defined as the presence of two or more CMDs, including type 2 diabetes (T2D), coronary heart disease (CHD), and stroke. Five indices were developed to assess IR levels: triglyceride-glucose (TyG) index, TyG-body mass index (TyG-BMI), TyG-waist circumference (TyG-WC), TyG-waist-height ratio (TyG-WHtR), and triglyceride to high-density lipoprotein cholesterol (TG/HDL-C) ratio. Cox proportional hazards and multi-state models were utilized to examine the associations between IR-related indices and CMM incidence and transition, respectively, with results expressed as hazard ratios (HRs) and 95% confidence intervals (CIs). The predictive utility of these indices was assessed using the net reclassification index (NRI) and integrated discrimination improvement index (IDI). Mediation analyses were conducted to quantify the potential mediating roles of biomarkers. Results During a mean follow-up period of 13.7 years, 5048 (1.3%) individuals developed CMM. Elevated baseline IR-related indices were associated with higher risks of incident CMM. The HRs (95% CIs) for each 1-standard deviation increase were as follows: 1.30 (1.26–1.34) for the TyG index, 1.42 (1.39–1.46) for the TyG-BMI, 1.54 (1.49–1.59) for the TyG-WC, 1.52 (1.48–1.57) for the TyG-WHtR, and 1.19 (1.17–1.21) for the TG/HDL-C ratio. Besides, TyG-WHtR and TyG-WC exhibited significantly higher NRI and IDI, indicating superior predictive performance for CMM risk. These indices played critical yet distinct roles in the progression of CMM. For transitions from being free of CMDs to single CMDs, these indices had the strongest impact on T2D (all P < 0.001). Participants initially diagnosed with CHD were more likely to progress to CMM when exposed to higher IR-related indices (all P < 0.001). The effect sizes for TyG-WC and TyG-WHtR were greater than those of other indices across all transitions. Mediation analyses revealed that biomarkers associated with liver function, renal function, and inflammation collectively mediated approximately one-third of the associations of the TyG-WHtR and TyG-WC indices with incident CMM. Conclusions Our findings highlight the critical role of IR-related indices, particularly TyG-WHtR and TyG-WC, in the incidence, progression, and prevention of CMM. The mediation effects of biomarkers indicate the potential for targeted interventions to reduce CMM risk in high-IR individuals.